Study on the dieback of mangrove forest system in The Bako National Park / Rabuyah Ni … [et al.] - Ni, Rabuyah; Chan, Margaret Kit Yok; Ngalai, Elly Lawai (2010)
The dieback in the mangrove forest in Bako National Park. Sarawak prompted an investigation on vegetation structure and the soil characteristics as a preliminary study to provide useful information about the factors causing dieback on three dominant mangrove plant species and suggest conditions suitable for mangrove vegetation rehabilitation. Sampling was performed at four locations: Telok Assam, Telok Delima, Sg Serait and Telok Lakei based a line plot sampling method with ten sampling plots of area 100 m 2 each at a distance of 30 m between midpoints of the adjacent plots. Investigation on vegetation structure showed that each site had its own dominant species. Sonneralia alba commonly known as. the perepat occurred mainly at Sg Serait and Telok Delima and with severe dieback at Telok Assam.